Apathy as a determinant of health behaviors in older adults: Implications for dementia risk reduction - Fleur Harrison; Moyra E. Mortby; Karen A. Mather; Perminder S. Sachdev; Henry Brodaty (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2023)
Abstract INTRODUCTION Long‐term improvements in physical inactivity and other behavioral risk factors are integral to dementia risk reduction; however, sustained behavior change is challenging. Apathy, depression, and fatigue may impact engagement in health behaviors, but their presentation overlaps. This study investigates whether these symptoms are differentially associated with multiple health behaviors. METHODS In 1037 community‐dwelling older adults without dementia (aged 70–90, 55% women), regression analyses examined apathy, depression, and fatigue as predictors of health behaviors (physical activity, diet, alcohol, smoking) and a behavioral risk index. RESULTS Apathy was associated with reduced physical activity and alcohol use, and one or multiple behavioral risk factors. No or inconsistent relations were found between depression or fatigue and health behaviors. DISCUSSION Apathy is relevant to multiple health behaviors and should be considered when designing health promotion for older adults, including interventions for dementia risk reduction. Findings highlight the importance of distinguishing apathy from comorbid symptoms. Highlights Novel theory‐based perspective on behavioural risk factors for dementia. Higher apathy predicted less physical activity and alcohol use, and increased odds of lifestyle risk factors. Depressive symptoms were not associated with any health behavior. Apathy may be a determinant of multiple health behaviors in older adults, distinct from depression and fatigue. Considering apathy in precision prevention of dementia appears warranted.